Mechanisms Underlying Sex Differences in Cannabis Use - Calakos, Katina C. (Curr Addict Rep, 2017)
PURPOSE OF THE REVIEW: Cannabis is the most commonly used illicit substance worldwide. In recent decades, highly concentrated products have flooded the market, and prevalence rates have increased. Gender differences exist in cannabis use, as men have higher prevalence of both cannabis use and cannabis use disorder (CUD), while women progress more rapidly from first use to CUD. This paper reviews findings from preclinical and human studies examining the sex-specific neurobiological underpinnings of cannabis use and CUD, and associations with psychiatric symptoms. RECENT FINDINGS: Sex differences exist in the endocannabinoid system, in cannabis exposure effects on brain structure and function, and in the co-occurrence of cannabis use with symptoms of anxiety, depression and schizophrenia. In female cannabis users, anxiety symptoms correlate with larger amygdala volume and social anxiety disorder symptoms correlate with CUD symptoms. Female cannabis users are reported to be especially vulnerable to earlier onset of schizophrenia, and mixed trends emerge in the correlation of depressive symptoms with cannabis exposure in females and males. SUMMARY: As prevalence of cannabis use may continue to increase given the shifting policy landscape regarding marijuana laws, understanding the neurobiological mechanisms of cannabis exposure in females and males is key. Examining these mechanisms may help inform future research on sex-specific pharmacological and behavioral interventions for women and men with high-risk cannabis use, comorbid psychiatric disease, and CUD.